Women in Jihad Militarism according to Yusuf Al-Qardhawi Thought - M. Adli Azhari Lubis (Budapest International Research and Critics University, 2021)
This study aims to discuss the Women in Jihad Militarism according to Yusuf Al-Qardhawi Thought. In this study, the authors based on library research, which is normative research by collecting data, as well as references related to the research theme, namely the study of women in Islam and its relation to other aspects, especially in the field of research. Career and its relevance to the rule of law. After the required data is collected, the writer then classifies and analyzes it. The discussion of this research is literature research, using the necessary data based on the primary and secondary literatures used in this study are the works of Yusuf Qardhawi, especially those related to his thoughts about women and other works that support and discuss about the study of women from various other perspectives of thought. Other sources that will be used by researchers can also be taken from books, magazines, and journals related to what is being researched. As for obtaining this data, there are several sources that will be used, namely: Primary Data Source and Secondary Data Source. Women in military jihad according to Yusuf al-Qardhawi's views and their relationships with PP No.39 of 2010 concerning Soldier Administration, it can be concluded that: 1.That Yusuf al-Qardhawi is a scholar moderate giving space for women to take part in taking part in military activities. 2.Yusuf al-Qardhawi's thoughts on the legal consequences of women entering military jihad vary.